ANALYSIS OF THE EFFECTIVENESS OF ARTIFICIAL INTELLIGENCE IN THE FORMATION OF INTELLECTUAL CAPITAL OF ENTERPRISES - HLEMBYTSJKIJ, Oleksij (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the effectiveness of artificial intelligence (AI) in forming intellectual capital within enterprises, emphasizing its strategic role in enhancing competitiveness amid digital transformation. Intellectual capital, comprising human, structural, and social components, has become a key asset for organizations navigating rapidly changing market conditions. AI technologies offer innovative solutions for automating processes, managing knowledge, and driving innovation, thereby creating value across various business functions.The study highlights AI's ability to optimize operations, such as data analysis, decision-making, and workforce development, through advanced tools like neural networks and machine learning algorithms. These technologies enable enterprises to process large volumes of data, forecast market trends, and streamline decision-making processes. Specific applications include automating routine tasks, developing personalized training programs for employees, and enhancing customer relationship management. The research presents examples from sectors such as agribusiness, banking, and healthcare, showcasing how AI fosters operational efficiency, cost reduction, and innovation. For instance, AI-driven systems in agriculture optimize resource use, while in banking, they enhance transaction security and fraud detection.Despite these advantages, the integration of AI poses challenges. High implementation costs, a shortage of skilled professionals, and ethical concerns, including data privacy risks, are significant barriers. Additionally, the dependency on AI for critical processes introduces vulnerabilities related to system failures and cyberattacks. The article underlines the importance of addressing these challenges through targeted investments in employee training, ethical AI development, and robust digital infrastructure.The findings suggest that AI adoption substantially impacts intellectual capital by fostering structured knowledge management, accelerating innovation, and improving productivity. However, a comprehensive approach involving ethical standards, regulatory frameworks, and interdisciplinary collaboration is essential for sustainable AI integration. The study concludes by recommending further research on AI's long-term socio-economic effects and its potential in conjunction with emerging technologies like blockchain and quantum computing.
Keywords: artificial intelligence; intellectual capital; digital transformation; automation; innovation; competitiveness; data privacy